On the phenology of protists: recurrent patterns reveal seasonal variation of protistan (Rhizaria: Cercozoa and Endomyxa) communities in tree canopies. Issue 7 (12th June 2021) - Walden, Susanne; Jauss, Robin-Tobias; Feng, Kai; Fiore-Donno, Anna Maria; Dumack, Kenneth; Schaffer, Stefan; Wolf, Ronny; Schlegel, Martin; Bonkowski, Michael
ABSTRACT: Tree canopies are colonized by billions of highly specialized microorganisms that are well adapted to the highly variable microclimatic conditions, caused by diurnal fluctuations and seasonal changes. In this study, we investigated seasonality patterns of protists in the tree canopies of a temperate floodplain forest via high-throughput sequencing with group-specific primers for the phyla Cercozoa and Endomyxa. We observed consistent seasonality, and identified divergent spring and autumn taxa. Tree crowns were characterized by a dominance of bacterivores and omnivores, while eukaryvores gained a distinctly larger share in litter and soil communities on the ground. In the canopy seasonality was largest among communities detected on the foliar surface: In spring, higher variance within alpha diversity of foliar samples indicated greater heterogeneity during initial colonization. However, communities underwent compositional changes during the aging of leaves in autumn, highly reflecting recurring phenological changes during protistan colonization. Surprisingly, endomyxan root pathogens appeared to be exceptionally abundant across tree canopies during autumn, demonstrating a potential role of the canopy surface as a physical filter for air-dispersed propagules. Overall, about 80% of detected OTUs could not be assigned to known species—representing dozens of microeukaryotic taxa whose canopy inhabitants are waiting to be discovered. Abstract : Investigation into the seasonality of protistan communities colonizing different microhabitats across the surface of tree canopies in a temperate floodplain forest.